Urgensi Pluralisme dalam Tatanan Hukum Islam di Indonesia - Ikram, Muhammad Furqanul; Gassing, Qadir; K, Kurniati (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
Diversity is a sunnatullah that every community must contemplate and believe in. Awareness of religious communities is the key to continuity in practicing their respective religions. Every religion has a substance of truth, in preennial philosophy a concept in philosophical discourse that discusses the nature of God as an absolute being is the source of all sources of existence. Pluralism is a condition of a pluralistic society (related to social and political systems) or a cultural condition of various different cultures in a society, or a situation where large groups and small groups can maintain their identity in society without having to oppose the dominant culture. This research is qualitative in nature so the method used is a qualitative method, where the focus of the research is centered on in-depth observation. In this research, data collection was carried out using the library study method, namely searching authentic written sources. Furthermore, the data that was successfully collected was analyzed to be able to understand and reach conclusions in this research.